2017
DOI: 10.31384/jisrmsse/2017.15.1.1
|View full text |Cite
|
Sign up to set email alerts
|

Job Stress and Work Performance of Marketing Professionals

Abstract: Marketing professionals are under a great deal of stress due to many antecedents of stress such as overload, role ambiguity, role conflict, responsibility, participation, etc. The stress badly affects the physical, cognitive and behavioural health and also effects professionalism as well as person's consistency in the environment and acceptance to change .The outcomes of stress is also seen on work performance. This study examines the relationship between job stress and work performance by using (n=3200) data … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2021
2021
2021
2021

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 5 publications
0
1
0
Order By: Relevance
“…A literature review showed that to date only descriptive research has been conducted, and “not a single study addressed positive emotional responses and only one research study focused on an in-depth analysis of the most commonly used coping strategies by journalists” (Monteiro et al , 2016, p. 751). In marketing, an increased risk of stress due to overload, role ambiguity and high expectations has been identified and indicated that performance decreases among stressed marketers (Ayaz et al , 2017; Noor and Maad, 2008; Perrewé and Harms, 2019). However, since communication work often takes place in project-based relationships (e.g.…”
Section: Literature Review: Stress Resilience In Communication Managementmentioning
confidence: 99%
“…A literature review showed that to date only descriptive research has been conducted, and “not a single study addressed positive emotional responses and only one research study focused on an in-depth analysis of the most commonly used coping strategies by journalists” (Monteiro et al , 2016, p. 751). In marketing, an increased risk of stress due to overload, role ambiguity and high expectations has been identified and indicated that performance decreases among stressed marketers (Ayaz et al , 2017; Noor and Maad, 2008; Perrewé and Harms, 2019). However, since communication work often takes place in project-based relationships (e.g.…”
Section: Literature Review: Stress Resilience In Communication Managementmentioning
confidence: 99%